SPE Annual Technical Conference and Exhibition 1999
DOI: 10.2118/56880-ms
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Proppant Flowback Phenomena Using a Large Scale Fracturing Simulator

Abstract: This paper evaluates the maximum flow rate before the sand production initiates while flowing back a reservoir after the hydraulic fracturing treatment. The experiments are performed in a high pressure slot which simulates a fracture. The slot is a parallel plate device, which is 7 ft high and 9 1/3 ft long with provisions for varying fracture gap width. The slot is filled with proppant to simulate a propped fracture, then, the closure pressure is applied with 12 actuators to simulate confining pressure on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…The FFCF study shows that there is a critical flow rate beyond which the sand will be produced from the propped fracture; below this rate, there is negligible sand production. 25 This result disproves Stein's 26 conclusion that the unconsolidated sand would flowback at any flow rate.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…The FFCF study shows that there is a critical flow rate beyond which the sand will be produced from the propped fracture; below this rate, there is negligible sand production. 25 This result disproves Stein's 26 conclusion that the unconsolidated sand would flowback at any flow rate.…”
mentioning
confidence: 74%
“…Previous numerical and experimental investigations of the flowback phenomena concluded that a proppant pack is stable when the range of the ratio of the fracture width to proppant diameter is between the values from three to six. [27][28][29] But these studies did not observe that these ratios are dependent on the cleanup flow rates; on the other hand, the FFCF results 25 show that the proppant flowback can occur within the recommended ratios, albeit at higher fluid rates as compared to the rates for the higher ratios.…”
mentioning
confidence: 78%
“…The number of applied stress cycles and the initial RCP pack strength appear to be the dominant factors that govern proppant back-production. Goel and Shah [11] investigated proppant flowback phenomena using a large-scale fracturing simulator. Experimental results show that flowback initiates at lower cleanup rates when the closure stress increases or when the fracture width increases and flowback initiates at higher cleanup rates when the sand size increases.…”
Section: Introductionmentioning
confidence: 99%
“…They observe that packs with width/grain diameter larger than 6 are inherently unstable. Goel et al's5 experimental results indicate that this ratio depends on closure stress, with higher values corresponding to lower closure stresses. All of the above analyses are based on simplified fracture models, where proppant beds are formed horizontally and gravity actually helps keep the proppant in place.Experimental results also show the presence of a critical flow rate through the pack above which the pack becomes unstable.…”
mentioning
confidence: 97%